UV-cured high-temperature-resistant resin for thermal runaway protection material and application of UV-cured high-temperature-resistant resin

By using UV curing thermal runaway protection materials of high temperature resistant resin and chopped fibers in lithium/sodium batteries, the problem of material strength dropping in the prior art at high temperatures is solved, and effective protection against high temperatures of 400-500℃ is achieved, which is significantly Improves battery safety and thermal insulation.

CN119119374APending Publication Date: 2024-12-13YANGTZE OPTICAL CHEMISTRY CO LTD +2
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411129345.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-16
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

Existing lithium/sodium batteries have the risk of fire and explosion in thermal runaway situations. Existing thermal management solutions such as aerogels, phase change materials and liquid cooling systems cannot effectively deal with thermal runaway problems under high temperature and high pressure, especially above 150℃. When the material strength decreases, the protective effect weakens.

Method used

UV curing high-temperature resistant resin is used to mix polysilazane and rigid framework materials, combined with chopped fibers and heat-absorbing materials, and prepare a thermal runaway protective material that can maintain strength at high temperatures of 400-500℃ to prevent heat transfer and Prevent adjacent batteries from heating up.

Benefits of technology

It significantly improves the safety of the battery, prevents fire and explosion caused by thermal runaway, maintains strength at high temperatures, avoids extrusion failure, and achieves effective heat insulation and protection of high temperatures.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119119374A_ABST
    Figure CN119119374A_ABST
Patent Text Reader

Abstract

The invention discloses UV (ultraviolet) curing high-temperature-resistant resin for a thermal runaway protection material and an application of the UV curing high-temperature-resistant resin. The UV-cured high-temperature-resistant resin is prepared from the following raw materials in percentage by mass: 20 to 50 percent of polybasic anhydride modified amino acrylate, 1 to 5 percent of pyromellitic dianhydride dimethyl acrylate glyceride, 5 to 20 percent of acrylate-epoxy compound, 10 to 50 percent of tris (2-hydroxyethyl) isocyanuric acid triacrylate, 15 to 30 percent of active monomer, 3 to 10 percent of bisphenol monoacrylate, 0.1 to 3 percent of photoinitiator and 0.01 to 0.3 percent of polymerization inhibitor. The raw materials also comprise 5-20% of light-cured polysilazane; the raw materials are mixed, stirred and reacted to obtain the high-density and high-strength UV-cured high-temperature-resistant resin. The UV-cured high-temperature-resistant resin can be mixed with chopped fibers and a heat absorption material to prepare a thermal runaway protection material capable of instantly coping with the high temperature of 400-500 DEG C, and the thermal runaway protection material is high in overall strength, prevents heat transfer and protects a battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of thermal runaway protection materials, and in particular relates to a UV-curable high-temperature resistant resin for thermal runaway protection materials and an application thereof. Background Art

[0002] The electrolyte and diaphragm components in existing lithium-ion batteries are flammable and explosive. In addition, the internal component distribution, uneven contact, or external thermal abuse, mechanical abuse, and electrical abuse of lithium-ion batteries during operation will cause short circuits in the battery, releasing a large amount of heat, causing the battery to heat up rapidly and thermal runaway, resulting in the release of toxic gases and smoke, fires, and even explosions, posing great risks. In large-scale energy storage equipment, thermal runaway of a single battery will trigger a chain reaction in adjacent batteries, ultimately causing a disaster. As the cost of raw materials for lithium-ion batteries continues to rise, sodium-ion batteries have become a research hotspot as a new generation of power batteries with lower theoretical costs, but sodium-ion batteries also have the problem of thermal runaway. This makes improving the safety of lithium / sodium batteries one of the important topics in the field of battery research.

[0003] The existing thermal management solutions are mainly as follows: (1) Using aerogel to separate each battery pack component. After a single battery pack has thermal runaway, the heat can be isolated within a limited range if it is not serious. However, aerogel cannot slow down the process of thermal runaway. When thermal runaway occurs, there is still a possibility of spillover to adjacent battery packs, resulting in continuous thermal runaway and fire or explosion. (2) Using phase change materials to manage the battery thermally. Usually, the phase change enthalpy value of phase change materials is only between 200 and 270 J / g, and after packaging, it is usually only between 100 and 200 J / g. Due to the low enthalpy value, phase change materials are usually used to maintain a constant operating temperature (such as 55°C) for the battery to maximize its performance, and cannot solve the problem of thermal runaway. (3) Installing a liquid cooling system on the battery and using a compressor to cool the battery. Due to the power limitation and feedback delay limitation of the compressor, the cooling efficiency of the liquid cooling system is limited and cannot cope with the instantaneous temperature rise.

[0004] Chinese patent CN116423939B discloses a thermal runaway protection material with rapid heat absorption and a preparation method thereof. The thermal runaway protection material is a laminated structure, which comprises, from top to bottom, a flame-retardant graphite thermal conductive film, a thermal conductive adhesive, a high thermal conductivity heat absorbing material, a thermal conductive adhesive and a flame-retardant graphite thermal conductive film. The peripheral sides of the laminated structure are all sealed with edge sealing adhesive. The thickness is designed according to the shape of the battery and the heat transferred is quickly absorbed to avoid being squeezed out by high temperature and high pressure, so as to achieve the purpose of rapid cooling. The material also has good strength, good flame retardancy, good vibration resistance, and a thermal conductivity coefficient of >1W.mK. A chemical change will occur between 60 and 400°C to absorb a large amount of heat (the endothermic enthalpy of the internal high thermal conductivity heat absorbing material is >1200J / g). A sufficient amount of thermal runaway protection material can reduce the maximum temperature of thermal runaway and prevent fire and explosion caused by high temperature.

[0005] However, different battery models require thinner thermal protection materials, and the organic support material must not soften or deform above 150°C to prevent the protective material from being squeezed out under high temperature and high pressure, which would weaken the thermal protection effect. As the energy density of power batteries increases, the temperature will get higher when thermal runaway occurs, so it is necessary to develop a thermal runaway protection material that can withstand high temperatures and maintain high strength at 150°C to prevent the material from being squeezed out and failing. Summary of the invention

[0006] In view of the above technical problems, the present invention provides a UV-curable high-temperature resistant resin for thermal runaway protection materials and its application. A high-strength and high-density UV-curable high-temperature resistant resin is prepared by mixing polysilazane and a material with a rigid skeleton. After mixing with chopped fibers and heat-absorbing materials, a thermal runaway protection material that can instantly cope with high temperatures of 400-500°C is prepared, which prevents heat from being transferred rapidly in battery cells, stops adjacent batteries from continuing to heat up, avoids the risks of fire and explosion, and significantly improves the safety of the battery.

[0007] In order to achieve the above-mentioned purpose, the present invention provides a UV-curable high-temperature resistant resin for thermal runaway protection materials, comprising the following raw materials in percentage by mass: 20-50% of polyacid anhydride-modified amino acrylate, 1-5% of pyromellitic dianhydride dimethacrylate, 5-20% of acrylate-epoxy compound, 10-50% of tris(2-hydroxyethyl)isocyanuric acid triacrylate, 15-30% of active monomer, 3-10% of bisphenol monoacrylate, 0.1-3% of photoinitiator and 0.01-0.3% of polymerization inhibitor.

[0008] Preferably, the UV-curable high temperature resistant resin further comprises 5-20% of photocurable polysilazane.

[0009] Preferably, the polyanhydride-modified aminoacrylate is obtained by a two-step temperature-raising reaction of polyanhydride, aminoacrylate and hydroxy acrylate in the presence of a catalyst and a polymerization inhibitor.

[0010] Further preferably, the reaction method is as follows: (1) Adding a catalyst and a polymerization inhibitor to polyacid anhydride and aminoacrylate while stirring, heating to 70-90°C and stirring for 1-2h to obtain a product; (2) Adding hydroxy acrylate, a catalyst and a polymerization inhibitor to the product, heating to 70-90° C. and stirring for reaction for 2-4 hours to obtain polyanhydride-modified amino acrylate; In step (1), the catalyst accounts for 0.01-0.2% of the total mass of the reaction system, and the inhibitor accounts for 0.01-0.2% of the total mass of the reaction system; In step (2), the catalyst accounts for 0.01-0.2% of the total mass of the reaction system, and the inhibitor accounts for 0.01-0.2% of the total mass of the reaction system.

[0011] The catalyst in steps (1) and (2) is p-toluenesulfonic acid, and the inhibitor is p-hydroxyanisole.

[0012] More preferably, the mass ratio of the polyacid anhydride to the aminoacrylate is 1:1-1:3; the mass ratio of the polyacid anhydride to the hydroxy acrylate is 1:0.1-1:0.8.

[0013] More preferably, the polyacid anhydride is trimellitic anhydride, mellitic acid anhydride, 3,6-dichlorotrimellitic anhydride, 1,2,4-cyclohexanetricarboxylic anhydride, 4-methacryloyloxytrimellitic anhydride, p-phenylene-diphenyltrimethylol dianhydride, ethylene glycol diphenyltrimethylol dianhydride, pyromellitic anhydride, 3,4,9,10-tetracarboxylic anhydride, 3,3',4,4'-biphenyltetracarboxylic anhydride, 2,2,3',3-biphenyltetracarboxylic anhydride, 1,2,3,4-cyclobutanetetracarboxylic anhydride, 2,3,6,7-naphthalenetetracarboxylic anhydride and 1,2,4,5-cyclohexanetetracarboxylic anhydride.

[0014] More preferably, the hydroxy acrylate is one or more of 2-hydroxyethyl acrylate, 2-hydroxypropyl acrylate, 3-hydroxypropyl acrylate, 2-hydroxybutyl acrylate, 4-hydroxybutyl acrylate, trimethylolpropane diacrylate, glycerol diacrylate, glycerol dimethacrylate, pentaerythritol triacrylate and dipentaerythritol pentaacrylate.

[0015] Preferably, the acrylate-epoxy compound is a substance containing both (meth)acrylate and epoxy bonds in its molecular structure.

[0016] Further preferably, the substance containing both (meth)acrylate and epoxy bond in the molecular structure is one or more of glycidyl methacrylate, glycidyl acrylate, (3,4-epoxycyclohexyl)methyl acrylate, 3,4-epoxycyclohexyl methyl methacrylate, epoxidized dicyclopentadiene acrylate and epoxidized cardanol acrylate.

[0017] Preferably, the active monomer is an acrylate monomer with functionality between 2 and 6.

[0018] Further preferably, the acrylate monomer with 2-6 functional groups is one or more of tricyclodecane dimethanol diacrylate, dioxane diol diacrylate, trimethylolpropane triacrylate, pentaerythritol triacrylate, pentaerythritol tetraacrylate, dipentaerythritol pentaacrylate and dipentaerythritol hexaacrylate.

[0019] Preferably, the bisphenol monoacrylate is 2-(2-hydroxy-3-tert-butyl-5-methylbenzyl)-4-methyl-6-tert-butylphenyl acrylate and / or 2-[1-(2-hydroxy-3,5-di-tert-pentylphenyl)ethyl]-4,6-di-tert-pentylphenyl acrylate.

[0020] Preferably, the photocurable polysilazane is PR132 type and / or PR105 type photocurable polysilazane.

[0021] Preferably, the photoinitiator is one or more of 4-benzoyl-4'-methyl-diphenyl sulfide (BMS), 2,4,6-trimethylbenzoyldiphenylphosphine oxide (TPO), 2,4,6-trimethylbenzoylphosphonic acid ethyl ester (TPO-L), bis(2,4,6-trimethylbenzyl acyl)phenylphosphine oxide (819), benzoin dimethyl ether (651), 2-methyl-1-(4-methylmercaptophenyl)-2-morpholine-1-propanone (907), 1-hydroxycyclohexyl benzophenone (184), 4-acryloyloxybenzophenone and methyl o-benzoylbenzoate (OMBB).

[0022] The present invention also provides a method for preparing a UV-curable high-temperature resistant resin for thermal runaway protection materials. The preparation method comprises adding each component into a reactor according to a proportion, stirring and reacting at 60-80° C. for 2-3 hours to obtain the UV-curable high-temperature resistant resin.

[0023] The present invention also provides an application of a UV-curable high temperature resistant resin for a thermal runaway protection material, wherein the application is to prepare the thermal runaway protection material, plant the thermal runaway protection material between batteries, and improve the passive safety of the batteries.

[0024] Preferably, the method for preparing the thermal runaway protection material is to mix raw materials of 71-95% by mass of heat-absorbing material, 0.5-3% by mass of chopped fiber, and 3-16% by mass of UV-curable high-temperature resistant resin, and obtain the thermal runaway protection material through hydraulic pressure, ultraviolet light curing, and polishing.

[0025] Further preferably, the heat-absorbing material is sodium acetate trihydrate, ammonium ferric oxalate trihydrate, citric acid monohydrate, citric acid, oxalic acid dihydrate, anhydrous oxalic acid, malonic acid, magnesium sulfate heptahydrate, zinc sulfate heptahydrate, succinic acid, maleic acid, fumaric acid, sodium carbonate decahydrate, calcium chloride hexahydrate, aluminum nitrate nonahydrate, ammonium pentaborate octahydrate, ammonium ferric sulfate dodecahydrate, ferrous chloride tetrahydrate, ammonium oxalate monohydrate, sodium tetraborate decahydrate, sodium tetraborate pentahydrate, aluminum sulfate 18hydrate, ammonium pentaborate, ammonium hydrogen borate tetrahydrate, boric acid, barium hydroxide octahydrate, sodium silicate pentahydrate, silicic acid, hydrated silicic acid, ammonium aluminum sulfate dodecahydrate, hydrated sodium aluminum silicate, potassium aluminum sulfate dodecahydrate, sodium sulfate decahydrate, copper sulfate heptahydrate, ferrous sulfate heptahydrate, cobalt chloride hexahydrate, calcium sulfate dihydrate, and the like. One or more.

[0026] More preferably, the heat-absorbing material is one or more of oxalic acid dihydrate, anhydrous oxalic acid, ammonium oxalate monohydrate, sodium acetate trihydrate, boric acid, ammonium pentaborate octahydrate, barium hydroxide octahydrate, sodium tetraborate decahydrate, potassium aluminum sulfate dodecahydrate, sodium sulfate decahydrate, calcium sulfate dihydrate, etc., and the mesh size is 80-300 mesh.

[0027] Further preferably, the chopped fibers are one or more of quartz chopped fibers, glass chopped fibers, plastic optical fibers, chopped optical fibers, etc., with a diameter of 3-300 μm and a length of 0.5-5 mm.

[0028] Further preferably, the irradiation power of the UV curing is >30 mW / cm 2 , irradiation dose>1J / cm 2 .

[0029] More preferably, the ultraviolet light comes from a high-pressure mercury lamp, a metal halide lamp, a 365nm UVLED lamp, a 385nm UVLED lamp, a 395nm UVLED lamp, a 405nm UVLED lamp or a composite ultraviolet lamp composed of a combination of the above ultraviolet lamps.

[0030] More preferably, the ultraviolet lamp is installed in a single-sided installation, an upper and lower surface aligned installation, or an upper and lower surface staggered installation.

[0031] The beneficial effects of the present invention are: 1. It contains polysilazane structure and a large number of rigid skeletons, has a high cross-linking density, and has high strength at high temperature; polyanhydride modified amino acrylate has excellent heat resistance, and there are residual carboxyl groups, which can further cross-link with epoxy bonds at high temperature to increase the cross-linking density, so that the high temperature resistance of UV-cured high temperature resistant resin is further improved. When it is used with short-cut fibers to prepare thermal runaway protection materials, it can enhance the overall strength of the material, instantly cope with high temperatures of 400-500°C, and prevent the thermal runaway protection material from being squeezed out and failing.

[0032] 2. Inorganic materials and organic materials are compounded to prepare thermal runaway protection materials, which achieves stable encapsulation of heat-absorbing materials. After being irradiated with ultraviolet light, the chopped fibers can guide ultraviolet light into the deep layer, achieving dual curing of the surface and deep layer, which meets the one-time curing and molding requirements of 50mm thick thermal runaway protection materials.

[0033] 3. The thermal runaway protection material prepared by the present invention has a high endothermic enthalpy value, and after the endothermic material is decomposed, the protection material will form a porous structure, becoming an excellent high-temperature resistant heat-insulating material, preventing heat from being transferred to adjacent batteries, preventing adjacent batteries from continuing to heat up, avoiding fire and explosion, and significantly improving the safety of the battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] Figure 1 Schematic diagram of the curing process of thermal runaway protection material.

[0035] Figure 2 Schematic diagram of the endothermic decomposition process of thermal runaway protection material.

[0036] Figure 3 This is a schematic diagram of the structure of the test experimental device in Example 12. DETAILED DESCRIPTION

[0037] The technical solution of the present invention is further explained below in conjunction with the accompanying drawings and specific embodiments. It is worth noting that the following embodiments are only preferred embodiments of the present invention and should not be construed as limiting the present invention. The protection scope of the present invention shall be subject to the contents recorded in the claims. Any modification or replacement made by a person skilled in the art to the technical solution of the present invention without creative work shall fall within the protection scope of the present invention.

[0038] In the following examples, the structural formulas of the raw materials are as follows:

[0039] Example 1 Preparation of polyanhydride-modified amino acrylate (1) 1 part of trimellitic anhydride, 2 parts of pyromellitic dianhydride and 7 parts of aminoacrylate (Dr. M451, Changxing Chemical Industry Co., Ltd.) were placed in a stirred reactor, stirred evenly, and then 0.01 parts of p-toluenesulfonic acid and 0.01 parts of p-hydroxyanisole were added. The mixture was stirred and heated to 80°C, and then reacted for 1.5 hours. The mixture was cooled to room temperature to obtain the product. (2) Add 1.6 parts of pentaerythritol triacrylate to the product, stir evenly, then add 0.005 parts of p-toluenesulfonic acid and 0.005 parts of p-hydroxyanisole, stir and heat to 75°C and react for 3 hours to obtain polyacid anhydride-modified amino acrylate D-1.

[0040] Example 2 Preparation of polyanhydride-modified amino acrylate (1) 5 parts of mellitic acid trianhydride and 5 parts of aminoacrylate (UN003, Zhongshan Qianyou Chemical Co., Ltd.) were placed in a stirred reactor, stirred evenly, and then 0.001 parts of p-toluenesulfonic acid and 0.001 parts of p-hydroxyanisole were added. The mixture was stirred and heated to 85°C for 2 hours, and then cooled to room temperature to obtain the product; (2) Add 0.5 parts of trimethylolpropane diacrylate to the product, stir evenly, then add 0.002 parts of p-toluenesulfonic acid and 0.002 parts of p-hydroxyanisole, stir and heat to 70°C and react for 3.5 hours to obtain polyacid anhydride modified amino acrylate D-2.

[0041] Example 3 Preparation of polyanhydride-modified amino acrylate (1) Place 1 part of 4-methacryloyloxy trimellitic anhydride, 1 part of p-phenylene-bis(triphenyl) dianhydride, 1 part of 1,2,4,5-cyclohexanetetracarboxylic acid dianhydride and 9 parts of aminoacrylate (HL-383, Wenzhou Hengli New Materials Co., Ltd.) in a stirred reactor, stir evenly, add 0.024 parts of p-toluenesulfonic acid and 0.024 parts of p-hydroxyanisole, stir and heat to 90°C for 1 hour, and cool to room temperature to obtain the product; (2) Add 1 part of 2-hydroxyethyl acrylate and 1.4 parts of 4-hydroxybutyl acrylate to the product, stir evenly, then add 0.028 parts of p-toluenesulfonic acid and 0.028 parts of p-hydroxyanisole, stir and heat to 70°C and react for 4 hours to obtain polyacid anhydride modified amino acrylate D-3.

[0042] Comparative Example 1 Take 1 part of trimellitic anhydride, 2 parts of pyromellitic dianhydride, 7 parts of amino acrylate (Dr-M451 of Changxing Chemical Industry Co., Ltd.), and 1.6 parts of pentaerythritol triacrylate and put them in a stirring reactor. After stirring evenly, add 0.015 parts of p-toluenesulfonic acid and 0.015 parts of p-hydroxyanisole. After stirring and heating to 80°C, react for 2 hours and cool to obtain polyacid anhydride modified amino acrylate D-4.

[0043] Comparative Example 2 The method and steps are the same as those in the example, except that the amounts of p-toluenesulfonic acid and p-hydroxyanisole in step (1) are changed to 0.03 parts; and the amounts of p-toluenesulfonic acid and p-hydroxyanisole in step (2) are changed to 0.01 parts, to prepare polyacid anhydride-modified aminoacrylate D-5.

[0044] Example 4 The polyanhydride-modified aminoacrylate prepared in Examples 1-3 and Comparative Examples 1-2 were respectively used to prepare UV-curable high temperature resistant resins, and the formula thereof is as follows: In terms of mass percentage, it includes 30.9% of polyanhydride-modified aminoacrylate, 3% of pyromellitic dianhydride dimethacrylate, 8% of acrylate-epoxy compound (glycidyl methacrylate), 20% of tris(2-hydroxyethyl)isocyanurate triacrylate, 5% of active monomer (trimethylolpropane triacrylate), 20% of active monomer (pentaerythritol tetraacrylate), 5% of bisphenol monoacrylate (2-(2-hydroxy-3-tert-butyl-5-methylbenzyl)-4-methyl-6-tert-butylphenyl acrylate), 5% of photocurable polysilazane (PR132 type, CSIC 718 Institute), 0.5% of photoinitiator (184), 1% of photoinitiator (4-acryloxybenzophenone), 1.5% of photoinitiator (TPO), and 0.1% of polymerization inhibitor (p-hydroxyanisole). Preparation method: Add the above raw materials into a reactor, heat to 60°C and stir to react for 3 hours to obtain UV-curable high temperature resistant resins, which are respectively recorded as NGW-1, NGW-2, NGW-3, NGD-1 and NGD-2.

[0045] The prepared UV-curable high temperature resistant resin was tested for hardness using a Shore durometer at room temperature (25°C ± 5°C), and then placed in an oven at 200°C and 300°C for constant temperature treatment for 20 minutes, respectively. The oven was then closed and the hardness was tested using a Shore durometer within 10 seconds. The results are shown in Table 1.

[0046] The prepared UV-curable high temperature resistant resin was treated at a constant temperature of 400°C for 30 minutes, and a thermal gravimetric experiment was performed. The thermal gravimetric data (weight reduction rate) were recorded. The results are shown in Table 1.

[0047] Table 1 Properties of UV-curable high temperature resistant resin serial number Hardness (25℃) Hardness (200℃) Hardness (300℃) Thermogravimetric data 1 NGW-1 92D 90D 85D 4.76% 2 NGW-2 91D 88D 83D 5.21% 3 NGW-3 91D 87D 84D 4.23% 4 NGD-1 86D 53D 47D 28.16% 5 NGD-2 78D 50D 43D 33.23% Example 5 A UV-curable high-temperature-resistant resin for thermal runaway protection material comprises, by mass percentage, 30.4% of polyanhydride-modified aminoacrylate D-1, 5% of pyromellitic dianhydride dimethacrylate, 12% of acrylate-epoxy compound (glycidyl methacrylate), 15% of tris(2-hydroxyethyl)isocyanurate triacrylate, 20% of active monomer (pentaerythritol triacrylate), 8% of bisphenol monoacrylate (2-[1-(2-hydroxy-3,5-di-tert-pentylphenyl)ethyl]-4,6-di-tert-pentylphenyl acrylate), 7% of photocurable polysilazane (PR105 type, China Shipbuilding Industry Corporation 718 Institute), 1.5% of photoinitiator (184), 1.0% of photoinitiator (819), and 0.1% of polymerization inhibitor (p-hydroxyanisole); the preparation method is the same as that of Example 4, and the prepared UV-curable high-temperature-resistant resin is recorded as NGW-4.

[0048] Example 6 A UV-curable high-temperature-resistant resin for thermal runaway protection materials comprises, by mass percentage, 20% of polyanhydride-modified aminoacrylate D-1, 5% of pyromellitic dianhydride dimethacrylate glycerol, 20% of acrylate-epoxy compound (3,4-epoxycyclohexylmethyl methacrylate), 30% of tris(2-hydroxyethyl)isocyanurate triacrylate, 15% of active monomer (tricyclodecane dimethanol diacrylate), 3% of bisphenol monoacrylate (2-(2-hydroxy-3-tert-butyl-5-methylbenzyl)-4-methyl-6-tert-butylphenyl acrylate), 6.89% of photocurable polysilazane (PR105 type, China Shipbuilding 718 Institute), 0.1% of photoinitiator (907), and 0.01% of polymerization inhibitor (p-hydroxyanisole); the preparation method is the same as that of Example 4, and the prepared UV-curable high-temperature-resistant resin is recorded as NGW-5.

[0049] Example 7 A UV-curable high temperature resistant resin for thermal runaway protection material, comprising polyanhydride-modified aminoacrylate D-1 by mass percentage 50%, pyromellitic anhydride dimethacrylate glycerol 1%, acrylate-epoxy compound (epoxidized dicyclopentadiene acrylate) 3%, acrylate-epoxy compound (epoxidized cardanol acrylate) 2%, tris(2-hydroxyethyl)isocyanurate triacrylate 10%, active monomer (tricyclodecane dimethanol diacrylate) 8%, active monomer (dioxane diol diacrylate) 8%, bisphenol monoacrylate ((2-(2-hydroxy-3-tert-butyl-5-methylbenzyl)-4-methyl-6-tert-butylphenyl acrylate) 4%, light-cured polysilazane (China Shipbuilding 718 Institute PR105 type) 12.7%, photoinitiator (BMS) 0.5%, photoinitiator (651) 0.5%, inhibitor (p-hydroxyanisole) 0.3%; the preparation method is the same as that of Example 4, and the prepared UV-curable high temperature resistant resin is recorded as NGW-6.

[0050] Example 8 A UV-curable high temperature resistant resin for thermal runaway protection material, having the same formula as that of Example 5, except that photocurable polysilazane is not used, to prepare a UV resin, which is recorded as NGW-7.

[0051] Comparative Example 3 A UV resin comprises, by mass percentage, 55.9% of epoxy acrylate (Sartomer CN120 NS), 30% of amino acrylate (M451 of Changxing Chemical Industry Co., Ltd.), 10% of active monomer (tripropylene glycol diacrylate), 1% of antioxidant (1135), 0.5% of photoinitiator (184), 1% of photoinitiator (4-acryloxybenzophenone), 1.5% of photoinitiator (TPO), and 0.1% of polymerization inhibitor (p-hydroxyanisole); the preparation method is the same as that of Example 4, and the prepared UV resin is recorded as NGD-3.

[0052] Comparative Example 4 A UV resin, having the same formula as Example 5, wherein the polyanhydride-modified aminoacrylate is replaced with an equal amount of aminoacrylate (M451 of Changxing Chemical Industry Co., Ltd.), is prepared to obtain a UV resin, which is designated as NGD-4.

[0053] Comparative Example 5 A UV resin having the same formula as in Example 5, except that the acrylate-epoxy compound is replaced by acrylate, is prepared to obtain a UV resin, which is designated as NGD-5.

[0054] Comparative Example 6 A UV resin having the same formula as that of Example 5 except that pyromellitic dianhydride dimethacrylate is not used is prepared to obtain a UV resin, which is recorded as NGD-6.

[0055] Comparative Example 7 A UV resin having the same formula as Example 4 except that tris(2-hydroxyethyl)isocyanurate triacrylate is not used is prepared to obtain a UV resin, which is designated as NGD-7.

[0056] Result detection: The hardness of the prepared UV resin was tested using a Shore durometer at room temperature (25℃±5℃), and then placed in an oven at 200℃ and 300℃ for constant temperature treatment for 20 minutes respectively. The oven was then turned off and the hardness was tested using a Shore durometer within 10 seconds. The results are shown in Table 2.

[0057] The prepared UV resin was kept at 400°C for 30 minutes for a thermal gravimetric test, and the thermal gravimetric data (weight reduction rate) were recorded. The results are shown in Table 2.

[0058] Table 2 Properties of UV resin serial number Hardness (25℃) Hardness (200℃) Hardness (300℃) Thermogravimetric data Example 1 NGW-1 92D 90D 85D 4.76% Example 5 NGW-4 93D 88D 82D 5.21% Example 6 NGW-5 92D 89D 84D 6.22% Example 7 NGW-6 91D 88D 84D 7.13% Example 8 NGW-7 91D 74D 65D 9.26% Comparative Example 3 NGD-3 90D 50D 20D 32.15% Comparative Example 4 NGD-4 81D 51D 32D 26.25% Comparative Example 5 NGD-5 88D 63D 38D 28.26% Comparative Example 6 NGD-6 83D 50D 46D 16.11% Comparative Example 7 NGD-7 91D 48D 22D 37.15% Example 9 A thermal runaway protection material, the formula of which is 90% potassium aluminum sulfate dodecahydrate, 3% chopped fibers, and 7% UV-curable high temperature resistant resin NGW-1 (prepared in Example 4) by mass percentage; wherein the chopped fibers are quartz chopped fibers; The preparation method is: (1) adding potassium aluminum sulfate dodecahydrate, chopped fibers and NGW-1 into a mixing reactor according to a mass ratio and stirring and mixing them uniformly to obtain a mixture; (2) Pour the mixture into a 199 mm × 154 mm × 2 mm mold and use the mold to press into shape under a hydraulic press; the mass of the mixture is 101.5 g and the pressure is 11 MPa; (3) After the pressed material is removed from the mold, place it under 100mW / cm 2 The irradiation was carried out under a metal halide lamp for 40 seconds, and the irradiation dose was 4J / cm 2 After CNC (numerical control machine tool) grinding, the thermal runaway protection material UV-N1 with a smooth surface is obtained.

[0059] Example 10 A thermal runaway protection material, wherein the formula is 38.5% of citric acid, 50% of magnesium chloride hexahydrate, 1.5% of chopped fibers, and 10% of UV-curable high temperature resistant resin NGW-2 (prepared in Example 4) in terms of mass percentage; wherein the chopped fibers are chopped glass fibers; The preparation method is the same as that of Example 9, wherein the feed mass in step (2) is 96.5 g and the pressure is 8.8 MPa, and a thermal runaway protection material UV-N2 with a flat and smooth surface is prepared.

[0060] Embodiment 11 A thermal runaway protection material, wherein the formula is 42% of citric acid, 50% of magnesium chloride hexahydrate, 2% of chopped fibers, and 6% of UV-curable high temperature resistant resin NGW-3 (prepared in Example 4) in terms of mass percentage; wherein the chopped fibers are chopped glass fibers; The preparation method is the same as that of Example 9, wherein the feed mass in step (2) is 1430 g and the pressure is 14.5 MPa; the irradiation time in step (3) is 80 s and the irradiation dose is 8 J / cm 2 ; The thermal runaway protection material UV-N3 with a smooth surface was prepared.

[0061] Example 12 A thermal runaway protection material, the formula of which is 92% potassium aluminum sulfate dodecahydrate, 1% chopped fibers, and 7% UV-curable high temperature resistant resin NGW-5 (prepared in Example 6) by mass percentage; wherein the chopped fibers are chopped glass fibers; The preparation method is the same as that of Example 9, wherein the feed mass in step (2) is 1500 g and the pressure is 16.2 MPa; the irradiation time in step (3) is 70 s and the irradiation dose is 7 J / cm 2 ; The thermal runaway protection material UV-N4 with a smooth surface was prepared.

[0062] Embodiment 13 A thermal runaway protection material, the formula of which is the same as that of Example 9, except that NGW-1 is replaced by NGW7 prepared in Example 8, to obtain a thermal runaway protection material UV-N5 having a flat and smooth surface.

[0063] Comparative Example 8 A thermal runaway protection material, having the same formula as in Example 9, except that NGW-1 is replaced by NGD-3 prepared in Comparative Example 3, and the preparation is the same as in Example 9, wherein the irradiation time in step (3) is 40 s, and the irradiation dose is 4 J / cm 2 ; The thermal runaway protection material UV-D1 with a smooth surface was prepared.

[0064] Comparative Example 9 A thermal runaway protection material, the formula and preparation method are the same as those of Example 9, only NGW-1 is replaced by Comparative Example 4 to prepare NGD-4, and a thermal runaway protection material UV-D2 with a flat and smooth surface is prepared.

[0065] Comparative Example 10 A thermal runaway protection material, the formula and preparation method are the same as those of Example 9, except that NGW-1 is replaced by Comparative Example 5 to obtain NGD-5, and a thermal runaway protection material UV-D3 with a flat and smooth surface is obtained.

[0066] Comparative Example 11 A thermal runaway protection material, the formula and preparation method are the same as those of Example 9, except that NGW-1 is replaced by Comparative Example 6 to obtain NGD-6, and a thermal runaway protection material UV-N4 with a flat and smooth surface is obtained.

[0067] Comparative Example 12 A thermal runaway protection material, the formula and preparation method are the same as those of Example 9, except that NGW-1 is replaced by Comparative Example 7 to prepare NGD-7, and a thermal runaway protection material UV-N5 with a flat and smooth surface is prepared.

[0068] Results: The thermal runaway protection materials prepared in Examples 9-13 and Comparative Examples 8-12 were tested for thermal conductivity according to ISO22007-2, and the enthalpy of the internal high thermal conductivity heat absorbing material was tested by differential scanning calorimetry, and the average thickness and density were measured. The results are shown in Table 3: Table 3 Performance parameters of thermal runaway protection materials serial number Thermal conductivity Enthalpy value of internal high thermal conductivity heat absorbing material density Average thickness Example 9 UV-N1 0.795W / (mK) 1495J / g <![CDATA[1.65g / cm 3 ]]> 2.03mm Example 10 UV-N2 0.762W / (mK) 1410J / g <![CDATA[1.56g / cm 3 ]]> 2.02mm Embodiment 11 UV-N3 0.745W / (mK) 1460J / g <![CDATA[1.58g / cm 3 ]]> 30.03mm Example 12 UV-N4 0.782W / (mK) 1392J / g <![CDATA[1.62g / cm 3 ]]> 30.10mm Embodiment 13 UV-N5 0.814W / (mK) 1536 J / g <![CDATA[1.63g / cm 3 ]]> 2.02mm Comparative Example 8 UV-D1 0.745W / (mK) 1465J / g <![CDATA[1.65g / cm 3 ]]> 2.03mm Comparative Example 9 UV-D2 0.797W / (mK) 1489J / g <![CDATA[1.54g / cm 3 ]]> 2.01mm Comparative Example 10 UV-D3 0.822W / (mK) 1518 J / g <![CDATA[1.57g / cm 3 ]]> 2.02mm Comparative Example 11 UV-D4 0.828W / (mK) 1465 J / g <![CDATA[1.58g / cm 3 ]]> 2.03mm Comparative Example 12 UV-D5 0.831W / (mK) 1448 J / g <![CDATA[1.56g / cm 3 ]]> 2.02mm Example 14 Application of thermal runaway protection materials in batteries (1) Build a test platform: Two soft-pack lithium iron phosphate batteries (Guangdong Jiatai New Energy Technology Co., Ltd.) with dimensions of 199*154*8.9mm, standard voltage of 3.2V, and fully charged capacity of 30AH, numbered as battery No. 1 and battery No. 2 respectively; (2) A heating plate with a power of 500 W is attached to the right side of battery No. 1 and fixed with two upper and lower fixing fixtures; a signal acquisition device is set on both battery No. 1 and battery No. 2 to collect the voltage of the two batteries and the temperature of the bonding surface of the two batteries and the thermal runaway protection material; (3) The thermal runaway protection materials prepared in Examples 9-13 and Comparative Examples 8-12 were sandwiched between Battery No. 1 and Battery No. 2 as the experimental group for testing the experimental device ( Figure 3 ); (4) Prepare a test experimental device without thermal runaway protection material as a blank group; replace the thermal runaway protection material with 2 mm thick glass fiber aerogel as a control group; (5) The test devices of the experimental group, blank group and control group were placed in an oven at a temperature of 50±2℃ for 12 hours, and the heating plate was powered on for heating. The heating plate temperature power was set to 100%, and the voltage and temperature of the battery were collected. When the voltage of battery No. 1 became 0V, the heating was stopped and the battery temperature was continued to be collected until the temperatures of the two batteries dropped below 50℃. The data collection was stopped. The results are shown in Table 4. The thermal conductivity coefficient was tested with reference to ISO 22007-2.

[0069] Table 4 Experimental data of thermal runaway protection materials in battery applications

[0070] Note: The thickness of UV-N1 and UV-N2 is 2mm, the thickness of UV-N3 and UV-N4 is 30mm, and the thickness of UV-D1~UV-D6 is 2mm.

[0071] It can be seen from Table 4 that when no thermal runaway protection material is used in the battery (blank group), battery No. 1 completely thermally runs away after being heated on the heating plate for 231s, and the maximum battery temperature reaches 442°C. At the same time, the adjacent battery No. 2 also experiences thermal runaway, and the maximum battery temperature reaches 425°C.

[0072] When glass fiber aerogel (control group) was used as the thermal runaway protection material, due to the thermal insulation effect of the aerogel, the internal temperature of battery No. 1 rose faster, and it went into complete thermal runaway after 175 seconds of heating. The maximum temperature reached 486°C, 54°C higher than the blank group. The adjacent battery No. 2 also experienced thermal runaway, with the maximum temperature reaching 433°C, 8°C higher than the blank group.

[0073] When using UV-N1 and UV-N2 with a thickness of 2mm as thermal runaway protection materials, the time for the voltage of battery No. 1 to drop to 0 is increased to more than 450s, which is almost 10% longer heating time than the blank group. At the same time, the maximum battery temperature during the entire test process is 322℃ and 313℃, respectively, which is more than 110℃ lower than the temperature of the blank group. In addition, the adjacent battery No. 2 has no thermal runaway, no protective material is squeezed out, and the thermal runaway protection effect is good.

[0074] When using UV-N4 and UV-N3 with a thickness of 30mm as thermal runaway protection materials, the time for the voltage of battery No. 1 to drop to 0 was nearly 1.5 times longer than that of the blank group. During the entire test process, the maximum temperature of the battery was 293°C and 307°C, respectively, which was more than 120°C lower than the temperature of the blank group. At the same time, the adjacent battery No. 2 had no thermal runaway and no protective material was squeezed out.

[0075] After the test, the thermal conductivity of UV-N1, UV-N2, UV-N3 and UV-N4 were all above 0.44W / (mK), indicating that they still had good thermal insulation effects, indicating that the materials had sufficient margin to meet thermal runaway, and the protective material close to battery No. 2 was basically not decomposed, and effectively blocked the heat from spreading to battery No. 2.

[0076] Comparative examples UV-D1~UV-D5 were used as thermal runaway protection materials. Due to the poor high temperature resistance of the encapsulation resin, some protective materials were squeezed out. Therefore, although the thermal runaway time was slowed down, the thermal runaway eventually spread to battery No. 2.

Claims

1. A UV-curable high temperature resistant resin for thermal runaway protection material, characterized in that: The invention comprises the following raw materials in percentage by weight: 20-50% of polyanhydride-modified amino acrylate, 1-5% of pyromellitic dianhydride dimethacrylate glycerol, 5-20% of acrylate-epoxy compound, 10-50% of tris(2-hydroxyethyl)isocyanurate triacrylate, 15-30% of active monomer, 3-10% of bisphenol monoacrylate, 0.1-3% of photoinitiator and 0.01-0.3% of polymerization inhibitor.

2. The UV-curable high temperature resistant resin for thermal runaway protection material according to claim 1, characterized in that: The UV curable high temperature resistant resin also includes 5-20% of photocurable polysilazane.

3. The UV-curable high temperature resistant resin for thermal runaway protection material according to claim 1, characterized in that: The preparation method of the polyanhydride modified amino acrylate is that polyanhydride, amino acrylate and hydroxy acrylate are subjected to two-step temperature-raising reaction under the action of a catalyst and a polymerization inhibitor to obtain the amino acrylate.

4. The UV-curable high temperature resistant resin for thermal runaway protection material according to claim 3, characterized in that: The preparation method comprises the following steps: (1) After the polyacid anhydride and amino acrylate are mixed, a catalyst and an inhibitor are added, and the mixture is stirred and heated to obtain a product; (2) Adding hydroxy acrylate, a catalyst and an inhibitor to the product, stirring and heating the product to obtain polyacid anhydride-modified amino acrylate.

5. The UV-curable high temperature resistant resin for thermal runaway protection material according to claim 4, characterized in that: The catalyst in steps (1) and (2) is p-toluenesulfonic acid, and the inhibitor is p-hydroxyanisole.

6. The UV-curable high temperature resistant resin for thermal runaway protection material according to claim 4, characterized in that: The amount of the catalyst and the inhibitor used in step (1) is 0.01-0.2% of the total mass of the polyacid anhydride and the amino acrylate; the amount of the catalyst and the inhibitor used in step (2) is 0.01-0.2% of the total mass of the product and the hydroxy acrylate.

7. The UV-curable high temperature resistant resin for thermal runaway protection material according to claim 4, characterized in that: The reaction temperature in step (1) is 70-90°C and the reaction time is 1-2h; the reaction temperature in step (2) is 70-90°C and the reaction time is 2-4h.

8. The UV-curable high temperature resistant resin for thermal runaway protection material according to claim 4, characterized in that: The mass ratio of the polyacid anhydride to the aminoacrylate in step (1) is 1:1-1:3; the mass ratio of the polyacid anhydride to the hydroxy acrylate in step (2) is 1:0.1-1:0.

8.

9. The UV-curable high temperature resistant resin for thermal runaway protection material according to claim 7, characterized in that: The polyacid anhydride is one or more of trimellitic anhydride, mellitic acid anhydride, 3,6-dichlorotrimellitic anhydride, 1,2,4-cyclohexanetricarboxylic anhydride, 4-methacryloyloxytrimellitic anhydride, p-phenylene-diphenyltrimethylol dianhydride, ethylene glycol diphenyltrimethylol dianhydride, pyromellitic anhydride, 3,4,9,10-tetracarboxylic anhydride, 3,3',4,4'-biphenyltetracarboxylic anhydride, 2,2,3',3-biphenyltetracarboxylic anhydride, 1,2,3,4-cyclobutanetetracarboxylic anhydride, 2,3,6,7-naphthalenetetracarboxylic anhydride and 1,2,4,5-cyclohexanetetracarboxylic anhydride.

10. The UV-curable high temperature resistant resin for thermal runaway protection material according to claim 9, characterized in that: The hydroxy acrylate is one or more of 2-hydroxyethyl acrylate, 2-hydroxypropyl acrylate, 3-hydroxypropyl acrylate, 2-hydroxybutyl acrylate, 4-hydroxybutyl acrylate, trimethylolpropane diacrylate, glycerol diacrylate, glycerol dimethacrylate, pentaerythritol triacrylate, and dipentaerythritol pentaacrylate.

11. The UV-curable high temperature resistant resin for thermal runaway protection material according to claim 1, characterized in that: The acrylate-epoxy compound is a substance containing both (meth)acrylate and epoxy bonds in its molecular structure; the active monomer is an acrylate monomer with 2-6 functionalities.

12. The UV-curable high temperature resistant resin for thermal runaway protection material according to claim 11, characterized in that: The substance containing both (meth)acrylate and epoxy bond in the molecular structure is one or more of glycidyl methacrylate, glycidyl acrylate, (3,4-epoxycyclohexyl)methyl acrylate, 3,4-epoxycyclohexylmethyl methacrylate, epoxidized dicyclopentadiene acrylate, and epoxidized cardanol acrylate; the 2-6 functional acrylate monomer is one or more of tricyclodecane dimethanol diacrylate, dioxane diol diacrylate, trimethylolpropane triacrylate, pentaerythritol triacrylate, pentaerythritol tetraacrylate, dipentaerythritol pentaacrylate, and dipentaerythritol hexaacrylate.

13. The UV-curable high temperature resistant resin for thermal runaway protection material according to claim 1, characterized in that: The bisphenol monoacrylate is 2-(2-hydroxy-3-tert-butyl-5-methylbenzyl)-4-methyl-6-tert-butylphenyl acrylate and / or 2-[1-(2-hydroxy-3,5-di-tert-pentylphenyl)ethyl]-4,6-di-tert-pentylphenyl acrylate.

14. The UV-curable high temperature resistant resin for thermal runaway protection material according to claim 2, characterized in that: The photocurable polysilazane is PR132 type and / or PR105 type photocurable polysilazane.

15. The UV-curable high temperature resistant resin for thermal runaway protection material according to claim 1, characterized in that: The photoinitiator is one or more of 4-benzoyl-4'-methyl-diphenyl sulfide, 2,4,6-trimethylbenzoyldiphenylphosphine oxide, 2,4,6-trimethylbenzoylphosphonic acid ethyl ester (TPO-L), bis(2,4,6-trimethylbenzyl acyl)phenylphosphine oxide, benzoin dimethyl ether, 2-methyl-1-(4-methylmercaptophenyl)-2-morpholine-1-propanone, 1-hydroxycyclohexyl benzophenone, 4-acryloyloxybenzophenone and methyl o-benzoylbenzoate.

16. A method for preparing a UV-curable high temperature resistant resin for thermal runaway protection material according to any one of claims 1 to 15, characterized in that: The components are stirred and heated to react to obtain a UV-curable high temperature resistant resin.

17. The preparation method according to claim 16, characterized in that: The reaction temperature is 60-80°C and the reaction time is 2-3h.

18. An application of the UV curable high temperature resistant resin for thermal runaway protection materials according to any one of claims 1 to 15, characterized in that: The application is to prepare thermal runaway protection materials.

19. The use according to claim 18, characterized in that: The method for preparing the thermal runaway protection material comprises mixing raw materials of 71-95% by mass of heat absorbing material, 0.5-3% by mass of short-cut fiber, and 3-16% by mass of UV-cured high-temperature resistant resin, and obtaining the thermal runaway protection material through molding and light curing.

20. The use according to claim 19, characterized in that: The heat absorbing material is one or more of sodium acetate trihydrate, ammonium ferric oxalate trihydrate, citric acid monohydrate, citric acid, oxalic acid dihydrate, anhydrous oxalic acid, malonic acid, magnesium sulfate heptahydrate, zinc sulfate heptahydrate, succinic acid, maleic acid, fumaric acid, sodium carbonate decahydrate, calcium chloride hexahydrate, aluminum nitrate nonahydrate, ammonium pentaborate octahydrate, ammonium ferric sulfate dodecahydrate, ferrous chloride tetrahydrate, ammonium oxalate monohydrate, sodium tetraborate decahydrate, sodium tetraborate pentahydrate, aluminum sulfate octahydrate, ammonium pentaborate, ammonium hydrogen borate tetrahydrate, boric acid, barium hydroxide octahydrate, sodium silicate pentahydrate, silicic acid, hydrated silicic acid, ammonium aluminum sulfate dodecahydrate, hydrated sodium aluminum silicate, potassium aluminum sulfate dodecahydrate, sodium sulfate decahydrate, copper sulfate heptahydrate, ferrous sulfate heptahydrate, cobalt chloride hexahydrate and calcium sulfate dihydrate; the chopped fibers are one or more of quartz chopped fibers, glass chopped fibers, plastic optical fibers and chopped optical fibers.

21. The use according to claim 20, characterized in that: The chopped fibers have a diameter of 3-300 μm and a length of 0.5-5 mm.

22. The use according to claim 19, characterized in that: The irradiation power during photocuring is >30mW / cm 2 , irradiation dose>1J / cm 2 .

Citation Information

Patent Citations

  • A rapidly heat-absorbing thermal runaway protection material and its preparation method

    CN116423939B